Topochemical Synthesis of Ca3CrN3H Involving a Rotational Structural Transformation for Catalytic Ammonia Synthesis - Cao, Yu; Kirsanova, Maria A.; Ochi, Masayuki; Al Maksoud, Walid; Zhu, Tong; Rai, Rohit; Gao, Shenghan; Tsumori, Tatsuya; Kobayashi, Shintaro; Kawaguchi, Shogo; Abou‐Hamad, Edy; Kuroki, Kazuhiko; et al. (Angewandte Chemie International Edition, 2022)
Topochemical reactions have led to great progress in the discovery of new metastable compounds with novel chemical and physical properties. With these reactions, the overall crystal structure of the host material is generally maintained. Here we report a topochemical synthesis of a hexagonal nitride hydride, h‐Ca3CrN3H, by heating an orthorhombic nitride, o‐Ca3CrN3, under hydrogen at 673 K, accompanied by a rotational structural transformation. The hydrogen intercalation modifies the Ca−N rock‐salt‐like atomic packing in o‐Ca3CrN3 to a face‐sharing octahedral chain in h‐Ca3CrN3H, mimicking a “hinged tessellation” movement. In addition, the h‐Ca3CrN3H exhibited stable ammonia synthesis activity when used as a catalyst. A topochemical synthesis route of a nitride hydride, h‐Ca3CrN3H is reported. It is interesting to observe a rotational structural transformation in a nitride‐based inorganic material. Furthermore, h‐Ca3CrN3H exhibits catalytic ammonia synthesis activity despite the lack of Ru/Fe centers.